Efficient polymer light-emitting diodes (PLEDs) based on chiral [Pt(C^N)(N^O)] complexes with near-infrared (NIR) luminescence and circularly polarized (CP) light. Issue 44 (29th October 2019) - Fu, Guorui; He, Yani; Li, Wentao; Wang, Baowen; Lü, Xingqiang; He, Hongshan; Wong, Wai-Yeung
Abstract : Chiral NIR-light emitters [Pt(iqbt)( S -L n ) ] (1–4 ) were used as dopants to produce CP-NIR-PLEDs displaying λ em of 732 nm, η MaxEQE of 0.87–0.93%, and g EL of up to 10 −3 . Abstract : Based on the molecular design of the chiral NIR emitters [Pt(iqbt)( S -L n )] (1–4 ), the first examples of CP-NIR-PLEDs with both attractive NIR-emission properties ( λ em = 732 nm; η MaxEQE = 0.87–0.93%) and high dissymmetry g EL factors up to 10 −3 are reported.